Optimization of HILIC method for the analysis of bisoprolol and its impurities considering uncertainties in peak position - Rakić Tijana; Jovanović Marko; Tumpa Anja; Jančić-Stojanović Biljana; Medenica Mirjana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
This paper presents the robust optimization of hydrophilic interaction liquid chromatographic method for the analysis of bisoprolol and its impurities A and C. Chemometric strategy is applied for detailed understanding of system's behavior and establishing the mathematical relationship between investigated factors (acetonitrile content in the mobile phase, pH of the water phase and buffer concentration in the water phase) and chromatographic responses. Grid point search methodology is then performed with the aim to identify the point with satisfactory separation quality for all analyzed substances and to achieve minimal analysis duration. Oversized chromatograms are made creating an extra band broadening for each chromatographic peak corresponding to the value of standard deviation in order to evaluate the incertitude originating from the model uncertainty. On the other hand, the uncertainty originating from the variation of experimental parameters is assessed by simulated experimental design robustness testing. Finally, the obtained robust optimal conditions were: chromatographic column Kinetex HILIC 100Å (100 mm x 4.5 mm, 2.6 mm particle size); mobile phase composed of acetonitrile - water phase (35 mM ammonium acetate, pH 4.9 adjusted with glacial acetic acid) (85:15 v/v); flow rate 1 mL min-1, column temperature 30°C and UV detection at 254 nm.